2008
DOI: 10.1007/s10551-008-9793-1
|View full text |Cite
|
Sign up to set email alerts
|

Global Standards and Ethical Stock Indexes: The Case of the Dow Jones Sustainability Stoxx Index

Abstract: DJSSI – Dow Jones Sustainability Stock Index, ethical stock indexes, SRI (Socially Responsible Investing), performance of SRI funds,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
141
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(157 citation statements)
references
References 16 publications
9
141
2
5
Order By: Relevance
“…Bauer et al (2004) used an international database containing 103 German, UK and US ethical mutual funds, and they found that when examining the investment style, there was no evidence of significant differences in risk-adjusted returns between ethical and conventional funds for the period 1990-2001. Contrariwise, Consolandi et al (2009), when conducting an event study on the Dow Jones Sustainability Stoxx Index (DJSI Stoxx), concluded that the evaluation of the CSP performance of a firm is a significant criterion for asset allocation activities over the period . However, Cheung (2011, found that announcement has not any significant impact on stock return, when he analysed the impact of Dow Jones World Index (DJSI World) firm inclusions and exclusions for a sample of US stocks over the period 2002-2008.…”
Section: Empirical Results On the Relationship Between Csp And Firm Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Bauer et al (2004) used an international database containing 103 German, UK and US ethical mutual funds, and they found that when examining the investment style, there was no evidence of significant differences in risk-adjusted returns between ethical and conventional funds for the period 1990-2001. Contrariwise, Consolandi et al (2009), when conducting an event study on the Dow Jones Sustainability Stoxx Index (DJSI Stoxx), concluded that the evaluation of the CSP performance of a firm is a significant criterion for asset allocation activities over the period . However, Cheung (2011, found that announcement has not any significant impact on stock return, when he analysed the impact of Dow Jones World Index (DJSI World) firm inclusions and exclusions for a sample of US stocks over the period 2002-2008.…”
Section: Empirical Results On the Relationship Between Csp And Firm Fmentioning
confidence: 99%
“…Therefore, consistent with prior literature (e.g. Freedman & Patten, 2004;Curran & Moran, 2007;Consolandi et al, 2009) the market model was chosen.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence both of a negative relation (López et al, 2007), no relation (Curran and Moran, 2007;García-Castro et al, 2010;Surroca et al, 2010) and a positive relation (Lo and Sheu, 2007;van Dijken, 2007;Consolandi et al, 2009;Cheung, 2010;Wagner, 2010) between CSP and CFP. López et al (2007) analysed whether there are significant differences in performance between firms which adopted sustainability practices, ratified by their belonging to the DJSI, and firms not included in the DJSI because they have not fulfilled its requirements.…”
Section: Corporate Sustainability and Corporate Performancementioning
confidence: 99%
“…the relation between CSP and firm performance use DJSI as a proxy for CSP (Lo and Sheu, 2007;López et al, 2007;Consolandi et al, 2009;Cheung, 2010).…”
Section: H3b2mentioning
confidence: 99%
“…Additionally, certain incentives motivating companies to pursue sustainability management can be identified which only impact stock index listed companies, such as the opportunity to be included in prestigious sustainability indices, like the Dow Jones Sustainability Index [69][70][71]. To control for the effect of being listed in well-known stock indices, another dummy variable was introduced indicating whether or not a company belongs to either the DAX or the MDAX, the two major German stock indices.…”
Section: Being Supportive Of Corporate Sustainability and The Applicamentioning
confidence: 99%